2015
DOI: 10.12924/johs2015.11010034
|View full text |Cite
|
Sign up to set email alerts
|

Educational Pathways to Remote Employment in Isolated Communities

Abstract: Abstract:Those who live in isolated communities often lack reliable, skilled employment opportunities, which fundamentally undermines their human security. For individuals who wish to remain in their isolated communities for family, religious, philosophical or other reasons, their attachment to their communities creates a disincentive for higher education. This promotes low educational achievement, which in turn results in low socioeconomic status, lack of social mobility, and a generational cycle of poverty. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Their investigation sought to understand whether this move to online learning could be leveraged to address long-term US workforce skills gaps, equitably and sustainably, and concluded that "these online platforms can provide an accessible and inclusive environment to learn new skills" [85]. Importantly, Dekenberger, Way, and Pearce [83] investigated how telework, along with remote training and education, can be combined to offer skilled employment opportunities to isolated communities. They concluded that the Internet has opened up many new telework and education opportunities to people choosing to remain in remote communities for family, religious, philosophical, or other reasons, and has the potential to help these people "out of poverty, reduce inequality overall, and provide those communities with viable means of employment security, now, and in the future" [83].…”
Section: Sdg 4: Quality Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Their investigation sought to understand whether this move to online learning could be leveraged to address long-term US workforce skills gaps, equitably and sustainably, and concluded that "these online platforms can provide an accessible and inclusive environment to learn new skills" [85]. Importantly, Dekenberger, Way, and Pearce [83] investigated how telework, along with remote training and education, can be combined to offer skilled employment opportunities to isolated communities. They concluded that the Internet has opened up many new telework and education opportunities to people choosing to remain in remote communities for family, religious, philosophical, or other reasons, and has the potential to help these people "out of poverty, reduce inequality overall, and provide those communities with viable means of employment security, now, and in the future" [83].…”
Section: Sdg 4: Quality Educationmentioning
confidence: 99%
“…Importantly, Dekenberger, Way, and Pearce [83] investigated how telework, along with remote training and education, can be combined to offer skilled employment opportunities to isolated communities. They concluded that the Internet has opened up many new telework and education opportunities to people choosing to remain in remote communities for family, religious, philosophical, or other reasons, and has the potential to help these people "out of poverty, reduce inequality overall, and provide those communities with viable means of employment security, now, and in the future" [83].…”
Section: Sdg 4: Quality Educationmentioning
confidence: 99%
“…First, the selection of closest positions between the coal and solar industry used was open to error and will in many cases be dependent on particular individual's interests along with specific job and training opportunities. This mobility of workers from one industry to another varies widely (Judy and D'Amico, 1997) although the ability for remote education is enabling more mobility in some sectors (Denkenberger et al, 2015). As noted earlier there is substantial online training possible in the solar industry.…”
Section: Limitations and Future Workmentioning
confidence: 99%
“…We can also link those results to the positive impacts of postsecondary education on Indigenous Canadians in terms of employment and income (Hull, 2005). Denkenberger et al (2015) have also highlighted the positive economic impact of postsecondary education for graduates in Northern communities.…”
Section: Discussionmentioning
confidence: 99%